2015
DOI: 10.1590/s1517-838246120131225
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae population dynamics in photobioreactors with secondary sewage effluent as culture medium

Abstract: Nitrogen and phosphorus present in sewage can be used for microalgae growth, possibiliting cost reduction in the production of microalgae at the same time that it decreases the eutrophication potential of the effluent. This research aimed at monitoring the native community of microalgae and coliform bacteria in a secondary effluent from anaerobic municipal sewage treatment. Two treatments (aerated and non-aerated) were performed to grow microalgae under semi-controlled conditions in semi-closed photobioreactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 55 publications
1
8
0
2
Order By: Relevance
“…However, for biofilm microalgal system, an average pH in the beginning of cultivation cycle was 7.51, and then the pH was rapidly increased up to an average of 8.92 after the first 2 days of cultivation time, but after that the pH was slowly decreased through the end of cultivation cycle and ended up with an average of 7.03 ( Table 1). These results are in agreement with the study of Marchello et al [38], which also found that pH had a tendency to increase when microalgae were growing due to a reduction of CO 2 in the system. Besides, the decreased pH in biofilm system could be explained by a lower phototrophic activity of microalgae, which possibly caused by the light and/or nutrients limitation.…”
Section: 3) Biomass Harvesting In Biofilm Systemsupporting
confidence: 93%
“…However, for biofilm microalgal system, an average pH in the beginning of cultivation cycle was 7.51, and then the pH was rapidly increased up to an average of 8.92 after the first 2 days of cultivation time, but after that the pH was slowly decreased through the end of cultivation cycle and ended up with an average of 7.03 ( Table 1). These results are in agreement with the study of Marchello et al [38], which also found that pH had a tendency to increase when microalgae were growing due to a reduction of CO 2 in the system. Besides, the decreased pH in biofilm system could be explained by a lower phototrophic activity of microalgae, which possibly caused by the light and/or nutrients limitation.…”
Section: 3) Biomass Harvesting In Biofilm Systemsupporting
confidence: 93%
“…Nitrogen and phosphorus present can be used for microalgae growth (organic pollutants into cellular constituents in lipid and carbohydrate forms) and possibly lead to cost reductions in the cultivation of microalgae. Chlorella vulgaris (C. vulgaris) was observed as one of the dominant microalgae strain by using sewage as the cultivation medium [3,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae releases some exudates which inhibit the growth of pathogenic microorganisms. Microalgal treatment is sustainable and efficient in the reduction of coliforms in effluent before being discarded from the sewage treatment plants [77].…”
Section: Wastewater Treatment and Nutrient Removalmentioning
confidence: 99%